2008
DOI: 10.1080/10705500801929742
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study on the multidimensional characteristics of the five-item psychological demands scale of the job content questionnaire

Abstract: The multidimensionality of the psychological demands scale should be considered in psychometric analysis and interpretation, occupational epidemiologic studies, and future scale extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…Tests for differential item functioning have applied in testing cross-language adaptations [23] and construct validity [24] of different occupational health questionnaires. In particular, DIF analyses have been used to evaluate scales from COPSOQ I [11] and in the development of COPSOQ II [3] as well as other scales [12,24]. The current paper extends upon this work by including tests for more variables -in particular a test for DIE with regard to important outcome variables.…”
Section: Discussionmentioning
confidence: 96%
“…Tests for differential item functioning have applied in testing cross-language adaptations [23] and construct validity [24] of different occupational health questionnaires. In particular, DIF analyses have been used to evaluate scales from COPSOQ I [11] and in the development of COPSOQ II [3] as well as other scales [12,24]. The current paper extends upon this work by including tests for more variables -in particular a test for DIE with regard to important outcome variables.…”
Section: Discussionmentioning
confidence: 96%
“…In the JCQ, the job-control scale includes two sub-components: decision authority (three items) and skill discretion (six items); the workplace social support dimension also contains two sub-components: supervisor support (four items) and coworker support (four items). Karasek's job-strain model has been widely used in job-stress research, often with strongly reliable, valid, and reproducible results 13,22) . The construct validity has been reported that the four factors extracted by the principal factor analysis (PCA) corresponded very closely to the theoretical constructs in the C-JCQ 13,22) .…”
Section: Chinese Version Of Job Content Questionnaire (C-jcq)mentioning
confidence: 99%
“…Karasek's job-strain model has been widely used in job-stress research, often with strongly reliable, valid, and reproducible results 13,22) . The construct validity has been reported that the four factors extracted by the principal factor analysis (PCA) corresponded very closely to the theoretical constructs in the C-JCQ 13,22) . In our study, Cronbach's alpha coefficients for the work demands subscale was 0.71, while that for the job control and workplace social support subscale was 0.69 and 0.81, respectively; there were no significant differences in reliability between genders.…”
Section: Chinese Version Of Job Content Questionnaire (C-jcq)mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the median of the job control scores with the JCQ was less than the one with the DCQ. In a similar way, the standard JCQ scale scoring method for the job demands is designed to equally balance the 2 sub-components of the job demands (J10-J11 and J12-J14) [45,46] so the 1st component (J10-J11) is given relatively more weight than the 2nd component (J12-J14), while the standard DCQ scoring method for job demands lacks such a balancing procedure. Karasek et al [9] reported a notable difference in the response distributions of 1 item of psychological job demands (JQ12 in the JCQ; and DQ9 in the DCQ) between the 2 questionnaires in the Swedish (Malmö) population sample.…”
Section: Discussionmentioning
confidence: 99%